Early detection of ventricular dysfunction by tissue Doppler echocardiography related to cardiac iron overload in patients with thalassemia - Suchaya Silvilairat (2020)
© 2020, Springer Nature B.V. Cardiac T2* MRI is used as a gold standard for cardiac iron quantification in patients with transfusion-dependent thalassemia (TDT). We hypothesized that left ventricular (LV) diastolic dysfunction would reflect the severity of iron overload and can serve as an early detection of cardiac iron deposits. A study was conducted on all patients with TDT. Hemoglobin, serum ferritin and non-transferrin bound iron, together with a complete echocardiography and cardiac T2* MRI, were performed on all patients. Seventy-seven patients with TDT were enrolled (median age 14 years). In the patient group with a mean serum ferritin of > 2500 ng/mL during the past 12 months, there were more patients with severe cardiac iron deposits than in the group with a mean serum ferritin of ≤ 2500 ng/mL. Diastolic dysfunction was absent in all patients with a serum ferritin of < 1000 ng/mL. All patients with cardiac T2* ≤ 20 ms had grade III LV diastolic dysfunction. However, twenty-one percent of patients with cardiac T2* > 20 ms had LV diastolic dysfunction. The differences observed in pulmonary vein atrial reversal duration and mitral A-wave (PVAR–MVA) duration ≥ − 1 ms and an E/E′ ratio ≥ 11 were proven to be the associated factors with the cardiac T2* ≤ 20 ms. Increased PVAR–MVA duration and increased E/E′ ratio reliably reflected a severe iron overload, according to a cardiac T2* in patients with TDT. LV diastolic dysfunction can occur prior to severe cardiac iron deposition. Tissue Doppler echocardiography has the potential for the early detection of cardiac involvement in patients with TDT.